Phytochemical determination and antibacterial activity of Punica granatum peel extracts against plant pathogenic bacteria - Khaleel, Ayad Ismael; Sijam, Kamaruzaman; Rashid, Tavga Sulaiman; Ahmad, Khairulmazmi (Scientific Research Publishing, 2016)
Plant pathogenic bacteria are recognized to be harmful microbes able to decrease the quantity and quality of crop production in the world. Punica granatum peel was screened for its potential use as biological control agent for plant pathogenic bacteria. P. granatum peel was successfully extract using n-hexane, methanol and ethyl acetate by maceration. The highest yield obtained by ethyl acetate showed that ethyl acetate extracted more compounds that readily soluble to methanol and n-hexane. For in-vitro antibacterial activity, three different species of plant pathogenic bacteria were used namely Erwinia carotovorum subsp. Carotovorum, Ralstonia solanacearum, and Xanthomonas gardneri. For all crude extracts, four different concentrations 25, 50, 100 and 200 mg/ml were used in cup-plate agar diffusion method. Streptomycin sulfate at concentration 30 μg/ml was used as positive control while each respective solvent used for peel extraction was used as negative control. The results obtained from in vitro studies showed only ethyl acetate extract possessed antibacterial activity tested on the plant pathogenic bacteria. Methanol and n-hexane did not show any antibacterial activity against plant pathogenic bacteria selected where no inhibition zones were recorded. R. solanacearum recorded the highest diameter of inhibition zones for all range of concentrations introduced followed by E. carotovorum subsp. Carotovorum and X. gardneri. For the minimum inhbitory concentration (MIC) and minimum bactericidal concentration (MBC), only the ethyl acetate extract was subjected to the assay as only ethyl acetate extract exhibited antibacterial activity. The minimum concentration of ethyl acetate extract that was able to inhibit plant pathogenic bacteria was recorded at a concentration of 3.12 mg/ml which inhibited R. solancearum and E. carotovorum subsp. Carotovorum, followed by X. gardneri at concentration 6.25 mg/ml. For the minimum bactericidal concentration (MBC), the results showed that at the concentration of 12.5 mg/ml, the extract was still capable of killing the pathogenic bacteria, R. solanacearum, and P. caratovora sub.sp. caratovora while for the bacteria X. gardneri, the concentration that was able to kill the bacteria was 25 mg/ml. The qualitative estimation of phytochemical constituents within P. granatum L. ethyl acetate peel extracts had revealed the presence of tannins, flavonoids, phenols alkaloid, Saponins, and terpenoids. This study has demonstrated that Ethyl Acetate peel extracts of P. granatum has significant antibacterial activity against pathogenic plant bacterial, and it could be of high agricultural value.